(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Jigme, Yangchen K. 2023. Ethnobotanical study of the wild edible plants used by the indigenous people of Merak in Bhutan. Asian J Ethnobiol 6: 1-6. Merak communities possess one of the oldest and most extensive cultural traditions of using plants for various ethnobotanical purposes, but this traditional knowledge still needs to be reported. As a result, this is the first ethnobotanical survey on Wild Edible Plants (WEPs) in Merak Gewog, Tashigang Dzongkhag, Bhutan. The data was obtained through an ethnobotanical survey and semi-structured interviews with 40 informants. The study identified 16 plant species from 16 genera and 16 families of WEPs consumed in Merak Gewog. Herbs (14 species) were found to be the most important sources, followed by shrubs (1 species) and trees (1 species). The most commonly consumed plant part(s) are leaves (8 species), followed by flowers (4 species), shoots and whole plant (with 3 species each), rhizome, and root (1 species each). Wild edible plants supplement the family diet, and their usage and collecting frequency are constrained by seasonal availability. Summer is the best time to harvest wild edible plants, followed by spring, autumn, and winter. However, many of the wild edible plants found in the Merak are under increased strain due to human and socioeconomic causes such as livestock overgrazing, habitat degradation, unsustainable harvesting, and forest fire. This finding has resulted in the disappearance of WEP species and the underlying indigenous knowledge. As a result, the importance of wild vegetables must be stressed and included in conservation and food security strategies.